Degradation of residual dyes in actual textile wastewater using UV/H2O2: Evaluation of the impact of operating variables through multi-layer perceptron analysis - Son, Chae Young; Kang, Jin Kyu; Lee, Youn Jun; Lee, Chang Gu; Kim, Jun; Park, Seong Jik; Cho, Young Moo; Shin, Gwy Am (Environmental Engineering Research, 2024)
UV/H2O2 is a commonly used advanced oxidation process for removing non-biodegradable organic compounds. However, additional efforts are needed to understand the relative significance of operational factors during the UV/H2O2. Here, we investigated the effect and specific contribution of crucial factors such as H2O2 concentration, UV intensity, and reaction time on the color and total organic carbon (TOC) removal efficiency in textile wastewater using the one-factor-at-a-time method and multi-layer perceptron (MLP) analysis. The results showed that color removal was enhanced with high H2O2 concentration, high UV intensity, and long reaction time. Overall, more than 99% removal of color was achieved by the UV/H2O2, utilizing the following parameters: H2O2 concentration of 5 mM, UV intensity of 26.6 W/m2, and reaction time of 180 min. On the other hand, the removal of TOC was increased by high H2O2 concentration and long reaction time, but not by high UV intensity. In the MLP analysis, the H2O2 concentration was identified as the primary factor affecting both color and TOC removal, accounting for 43% and 50% reduction of the color and TOC, respectively. Overall, this study helps to understand the relative importance of the most critical operating factors in treating actual textile wastewater by the UV/H2O2.
Keywords: Actual textile wastewater; Color removal; H 2O 2; Multi-layer perceptron; Multilayers perceptrons; Textile wastewater; Total Organic Carbon; Total organic carbon removal; UV intensity; UV/H2O2; Actual textile wastewater; Color removal; Multi-layer perceptron (MLP); TOC removal; UV/H2O2